Um es tudo sobre as condições de acess ibilidade em pré-es colas - Corrêa, Priscila Moreira [UNESP]; Manzini, Eduardo José (FapUNIFESP (SciELO), 2012)
The use of a specific instrument is essential for educators to be able to analyze the conditions of physical accessibility of their schools. This paper aims to present results obtained by applying a protocol for assessing the physical accessibility in six pre-schools in a city in the the interior of the state of São Paulo. This protocol is composed by eight routes used by students circulating inside the pre-school and also for items regarding the established routes that should be evaluated by the educators. The criteria used to select the six schools that were evaluated were: 1) year the school was constructed, 2) region, and 3) availability of educational services for students with physical disabilities or visual and / or multiple disabilities. The evaluation of the schools enabled the analysis of accessibility conditions according to: types of entrance gates, doors, floor/pavement, obstacles, width of corridors, pathway inclination, sports court, sand box, soccer field, water fountain, and bathroom. The results showed that it was possible to compare and distinguish conditions of accessibility of each item of the protocol for each of the six assessed schools. The protocol that was developed enables professionals in specialized educational services to perform their tasks, that is, to identify, develop and organize pedagogical and accessibility resources.
A study about accessibility conditions in pre-schools
Keywords: Accessibility; Evaluation instruments; Special education